The COVID-19 Pandemic and Bioethical Challenges for Research with Human Beings - Denisse Isabel Suaste Pazmiño; Kathya Verónica Suaste Pazmiño (Medisur)
Since 2020, the appearance of COVID-19 has revealed multiple challenges for bioethics, due to the rush to find a treatment or vaccine to combat this disease, however, this is not a justification for exceeding bioethical limits. Dignity is an inherent value of the human being, which is protected by bioethical principles and other principles such as equity, transparency and proportionality, to support each of the parts of the investigation. The objective of this study is to describe the bioethical challenges in research in humans during the COVID-19 pandemic. A search was carried out for scientific articles and material published between 2020 and 2022, both from scientific journals and from government health institutions and bioethics societies. Twenty-one articles that met the established criteria were selected. The importance of the role played by the research ethics committees to regulate interventions in humans and avoid the violation of the rights, dignity and integrity of the participating subjects in order to generate positive results for the entire population was evident.